Peran Sistem Informasi Akuntansi Dalam Pengendalian Internal Persediaan Bahan Baku Pada PT. Indopintan Sukses Mandiri Semarang - Khairul Aziz Sardana Putra; Sodikin Manaf (Jurnal Ekonomi Manajemen Akuntansi, 2021)
Indopintan Sukses Mandiri is a company engaged in electronic assembly. Accounting information systems have a close relationship with inventory control. In recording the raw materials of PT. Indopintan Sukses Mandiri implements a perpetual recording system, which is a recording of the amount of inventory that is carried out every time there is a transaction. so that the amount of inventory available at any time can be known. The recording of these raw materials is carried out by the bookkeeping department and the warehouse section. The purpose of this study was to determine the role of accounting information systems in internal control of raw material inventory. The research method uses interview and documentation techniques about the role of accounting information systems in internal control of raw material inventory. From the overall research results, the Accounting Information System for raw material inventory at PT. Indopintan Sukses Mandiri has been running quite effectively, seen from the preparation of clear procedures. The procedures for the Accounting Information System have been quite effective because the documents used for transactions have been serially numbered in print. Internal control is still less effective because there are still multiple functions in the reception and storage department.